Assessing the real significant research input & output among various academic fields - Yusof, Yushaida; Abdullah, Amalina; Mohd Said, Ridzwana; Sazili, Awis Qurni; Kamarudin, Norliyana; Tugiran, Yusnita; Esam, Asrizam (Global Illuminators Malaysia, 2018)
In Malaysia, the quality of the research and development (R&D) in Malaysia‟s universities is periodically evaluated according to guidelines and concept written in Malaysia Research Assessment (MyRA). It uses bibliometric measurement as a major part of the evaluation Bibliometric benchmarking criteria compared to the research output using a common range of indicators. As a consequence, the distributions of the indicators are not comparable across different disciplines. Considerable concern has been raised about their over‐reliance on international bibliometric and citation databases, e.g. Thomson‐ Reuters World of Science or Elsevier‐Scopus. These current indicators used tend to benefit the physical, life, and medical sciences, and engineering and not adequate when it comes to assessing accomplishment in the social science and humanities disciplines. Based on the drawbacks discussed, there is no „one size fits all‟ solution to the university research output evaluation process. In order to emulate a situation that encompasses various institutions‟ mission and vision, the research methodology of this study involves primary and secondary data collections from several UPMs‟ faculties of different background. The studies examined different types of research input and research output in social science research and humanities research. The input from the department managerial, top management, senior lecturer, and supporting staff from the Universiti Putra Malaysia (UPM) faculties and institute has been explored using a survey, Nominal Group Technique (NGT) and Focus Group Discussion (FGD), as a case study.